The influence of 3-hydroxy-2-naphthoic acid on agricultural wastes extracted sugar production used as energy sources. (1st September 2022) - Liu, Manqing; Zuo, Shida; Liang, Yunyi; Sheng, Yequan; Ge, Shengbo; Wu, Jinglei; Ma, Hongzhi; Sun, Fubao; Ahamad, Tansir; Le, Quyet Van; Xia, Changlei
Graphical abstract: Highlights: The addition of 3H2NA enhanced the glucose yield of the three agricultural wastes. 3H2NA can assist three kinds of pretreatment to improve enzymatic hydrolysis. The removal of xylan and lignin increased cellulose accessibility. Fiber fracture of corn stover was aggravated by 3H2NA in organosolv pretreatment. Glucose yield was optimized by combined severity factor and 3H2NA concentration. Abstract: The addition of 3-hydroxy-2-naphthoic acid (3H2NA) during dilute acid pretreatment of poplar has been proved to enhance enzymatic digestibility by inhibiting lignin repolymerization and adding carboxylic acid group on lignin. In this study, wheat straw (WS), corn stover (CS) and corn cob (CC) were used as raw materials to conduct dilute acid pretreatment with or without 3H2NA addition. Moreover, we examined the auxiliary effects of 3H2NA on dilute acid pretreatment, hot water pretreatment, and organosolv pretreatment of CS, respectively. The 72 h hydrolysis yield was enhanced by 61.31%, 18.94% and 13.58% during dilute acid pretreatment of WS, CS, and CC with the addition of 3H2NA, respectively. Moreover, the 72 h hydrolysis yield was enhanced by 30.11%, 29.30%, and 24.08% in dilute acid, hot water, and organosolv pretreatment of CS, respectively. In addition, the highest cellulose conversion rate was increased by 31.99% from 52.29% (without addition) to 69.01% by adding 2% (w/w) 3H2NA and 1% (w/w) H2 SO4 at 180 °C for 2 h. These results indicated that the addition of 3H2NA was beneficial for the efficiency of different pretreatment strategies (dilute acid, hot water, and organosolv pretreatments) and various agricultural residues (WS, CS, and CC), respectively.